Heat stress in Trematomus bernacchii: bias of experimental design - D Rizzotti; S Greco; M Gerdol; C Manfrin; G Santovito; A Pallavicini; PG Giulianini (-, 2020)
The studies on Trematomus bernacchii suggest that this shallow water benthic species has reduced ability to acclimate and tolerate warmer conditions, since like the other Antarctic marine organisms it adapted to the extreme and stable Antarctic sea. Understanding the effects of exposure of stenothermic species to prolonged sub-lethal heat stress is of extreme interest in the scenario of rising polar sea temperatures presented by climate change. This study evaluated the impact of a 1.5 °C temperature increase over 19 days on some hematological and transcriptomic parameters. Blood samples were obtained from heart, fixed and embedded in either acrylic or epoxy resin for ultrastructural analysis. The morphology of erythrocytes in semithin section was evaluated through the ImageJ shape descriptors. The mean erythrocytes circularity in control animals decreased from 0.810±0.034 to 0.672±0.079 after 19 days. The mean circularity in experimental ones changed from 0.820±0.030 to 0.626±0.051. The erythrocytes became more elliptical over the time during the experiment, regardless of the temperature of the water. The pairwise control-experimental comparisons of cells circularity are all non significant (p>0.05), whilst difference of cells circularity is already significant (p<0.05) by comparing freshly caught animals (0.911±0.018) and the control ones after 1 week of acclimation at the beginning of the experiment. Samples of gills, brain and muscle were also collected from specimens in all conditions in order to perform RNAseq analysis and study the response of T. bernacchii to temperature increase also from a transcriptomic point of view. A reference transcriptome was assembled with sequencing reads obtained from Short Read Archive, yielding promising results as quality and completeness were high: N50 = 1650 and BUSCO score against the Actinopterygii ortholog database (82.9% complete, 10% fragmented and 7% missing). Differential expression analysis are now in progress. These results highlight how biases in ...